Hazardous geomorphic processes in the extratropical Andes with a focus on glacial lake outburst floods - Iribarren Anacona, Pablo (2016)
This study examines hazardous processes and events originating from glacier and permafrost areas in the extratropical Andes (Andes of Chile and Argentina) in order to document their frequency, magnitude, dynamics and their geomorphic and societal impacts. Ice-avalanches and rock-falls from permafrost areas, lahars from ice-capped volcanoes and glacial lake outburst floods (GLOFs) have occurred in the extratropical Andes causing ~200 human deaths in the Twentieth Century. However, data about these events is scarce and has not been studied systematically. Thus, a better knowledge of glacier and permafrost hazards in the extratropical Andes is required to better prepare for threats emerging from a rapidly evolving cryosphere. I carried out a regional-scale review of hazardous processes and events originating in glacier and permafrost areas in the extratropical Andes. This review, developed by means of a bibliographic analysis and the interpretation of satellite images, shows that multi-phase mass movements involving glaciers and permafrost and lahars have caused damage to communities in the extratropical Andes. However, it is noted that GLOFs are one the most common and far reaching hazards and that GLOFs in this region include some of the most voluminous GLOFs in historical time on Earth. Furthermore, GLOF hazard is likely to increase in the future in response to glacier retreat and lake development. To gain insight into the dynamics of GLOFs I create a regional-scale inventory of glacier lakes and associated hazards in the Baker Basin, a 20500 km2 glaciated basin in the Chilean Patagonia. I also simulate and reconstruct moraine- and ice- dammed lake failures in the extratropical Andes using numerical and empirical models. More than 100 GLOFs have occurred in the extratropical Andes since the Eighteenth Century and at least 16 moraine-dammed lakes have produced GLOFs. In the extratropical Andes most of the failed moraine-dammed lakes were in contact with retreating glaciers and had moderate (> 8°) to steep ...